Neurological Basis of Dyslexia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Evidence of a neurological basis for developmental dyslexia is reviewed by a researcher from the Cognitive Neurology Laboratory, Department of Neurology, Marseille, France.